Recent advances in QoS provisioning in wireless ad hoc networks. (2017) - Srivastava, Prakash; Kumar, Rakesh
With rapid increase in multimedia and other real time applications, incorporating quality of service (QoS) requirements like end to end delay, bandwidth, jitter and energy in MANET is necessary. MANET has some unique features such as self-organising and easy deployment. It has great potential in many applications such as military and civil. Existing QoS aware routing protocols designed for wired networks cannot be directly applied to wireless ad hoc networks due to its dynamic topological scenario and error prone nature of these wireless links. Best-effort QoS routing protocols are needed to ensure optimum network operation in an unpredictable wireless environment. Besides, QoS routing also ensures that a network performance should not be degraded in the event of disruption of links, failure of mobile devices and short residual connectivity time. In this paper, comprehensive description of QoS routing along with its taxonomy is presented and different QoS routing proposals are analysed in terms of its performance and limitations.